Dynamic perspectives on globalization and sustainable business in Asia - Ordonez de Pablos, Patricia 1975- (IGI Global, 2019)
"This book brings together academics, researchers, lecturers, decision makers, policy makers, and practitioners to share new theories, research findings, and case studies, to enhance understanding and collaboration in business, management and technology in Asia now and in the future. The book focuses on Asia, with a special attention to South East Asian countries"--
Description based on title screen (IGI Global, viewed 10/06/2018)
Keywords: Sustainable development / Asia; Entrepreneurship / Environmental aspects / Asia; Globalization / Asia